2020
DOI: 10.1107/s2056989020011184
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of dichlorido-1κCl,2κCl-(μ2-3,5-dimethyl-1H-pyrazolato-1κN 2:2κN 1)(3,5-dimethyl-1H-pyrazole-2κN 2){μ-2-[(2-hydroxyethyl)amino-1κ2 N,O]ethanolato-1:2κ2 O:O}dicopper(II)

Abstract: The title compound, [Cu2(C5H7N2)(C4H10NO2)Cl2(C5H8N2)], is a pyrazolate aminoalcohol complex which contains two dimethylpyrazole molecules in monodentate and bidentate-bridged coordination modes and a monodeprotonated diethanolamine molecule. Both copper atoms are involved in the formation of non-planar five-membered chelate rings. One Cu atom is in a distorted tetrahedral environment formed by the pyridine nitrogen atom of the protonated dimethylpyrazole molecule, the N atom of the deprotonated bridged dimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The bond Cu-N distances range from 2.0115 (19) to 2.005 (2) Å and the Cu-Cl bond distance is 2.6548 (18) Å. These bond distances agree with those found in other complexes[18,19]. The cis X-Cu-Cl (X = N or O) angles in the CuO2N2Cl square pyramid range from 92.44(7)° to 99.91(7)°, while the X-Cu-O9 angles in the CuO3N2 square pyramid range from 80.2 (2)° to 112.1 (2)°.…”
supporting
confidence: 86%
“…The bond Cu-N distances range from 2.0115 (19) to 2.005 (2) Å and the Cu-Cl bond distance is 2.6548 (18) Å. These bond distances agree with those found in other complexes[18,19]. The cis X-Cu-Cl (X = N or O) angles in the CuO2N2Cl square pyramid range from 92.44(7)° to 99.91(7)°, while the X-Cu-O9 angles in the CuO3N2 square pyramid range from 80.2 (2)° to 112.1 (2)°.…”
supporting
confidence: 86%
“…We have surveyed the literature and have found that in several examples, the lengths of metal–oxygen bonds decrease as more negative charges are present on the O atom. For instance, Safarmamadov et al described the structure of [Cu 2 (C 5 H 7 N 2 )­(C 4 H 10 NO 2 )­Cl 2 (C 5 H 8 N 2 )] . In a free state, diethanolamine has two hydroxyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, there are a couple of examples that the lengths of metal–oxygen bond decrease as more negative charges localize on the oxygen atom. For example, Safarmamadov and co-workers reported the single-crystal structure of the copper dimethylpyrazole diethanolamine complex [Cu 2 (C 5 H 7 N 2 )­(C 4 H 10 NO 2 )­Cl 2 (C 5 H 8 N 2 )] . In the normal condition, diethanolamine possesses two OH groups.…”
Section: Results and Discussionmentioning
confidence: 99%
“…For example, Safarmamadov and co-workers reported the single-crystal structure of the copper dimethylpyrazole diethanolamine complex [Cu 2 (C 5 H 7 N 2 )(C 4 H 10 NO 2 )Cl 2 (C 5 H 8 N 2 )]. 46 In the normal condition, diethanolamine possesses two OH groups. Upon coordination with Cu 2+ , deprotonation takes place and one hydroxyl group is converted into O − .…”
Section: ■ Results and Discussionmentioning
confidence: 99%